Jurisprudence Analysis Of Religious Court Decisions On The Determination Of Guardians Due To Wali 'Adhal In Indonesia (Period 2006 – 2010) - Nurul Rizki Ananda; Widiya Yul (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
This study aims to analyze the pattern of judges' legal considerations, the factors that cause wali 'adhal, the tendency to form jurisprudence, and the quality of legal reasoning in the decisions of the Religious Courts in Indonesia for the period 2006–2010. The method used is a normative juridical approach with empirical analysis of 124 court decisions. The results of the study showed that most of the requests for the appointment of guardians were granted, which indicates a tendency for consistency of decisions (quasi-jurisprudence). The main factors that cause wali 'adhal are dominated by non-shari'i reasons such as economy, social status, and family conflicts. In terms of legal reasoning, judges use various approaches, namely deductive, teleological, and substantive, although deductive reasoning still dominates. The study also found that although rulings tend to protect women's rights, the quality of legal arguments still needs to be improved to be more comprehensive, contextual, and substantive justice-oriented.